Replacement of lip-split mandibulotomy by pull-through approach for T3–4 oral carcinomas. Issue 9 (September 2021) - Marhic, A.; Guerlain, J.; Benmoussa, N.; Breuskin, I.; Honart, J.-F.; Janot, F.; Moya-Plana, A.; Temam, S.; Gorphe, P.
Abstract: At the study hospital, the lip-split mandibulotomy (LSM) has progressively been replaced by a pull-through (PT) approach. This study compared the outcomes of the LSM and PT approaches in a series of 192 patients with T3–T4a oral tongue and floor of the mouth squamous cell carcinoma treated over the two last decades. No difference in margin status ( P  = 0.254), rate of early complications (local infections) ( P  = 0.867), haematoma/haemorrhage ( P  = 0.221), delayed wound healing ( P  = 0.438), re-operation ( P  = 0.083), or Clavien–Dindo classification (P= 0.5281) was found. The LSM approach was associated with a higher rate of late complications such as pseudarthrosis (14.5% vs 0.9%; OR 17.89, P  = 0.0005) and trismus (35% vs 13.8%; OR 3.32, P  = 0.025), and a trend towards a higher rate of fistulas (24.6% vs 13.1%; OR 2.16, P  = 0.088). The quality of life of long-term survivors (median 132 months) was similar in the two groups, with a mean QLQC30 score of 59.7 ( P  = 0.099) and mean MDADI score of 57.4 ( P  = 0.213). The 5-year local control rate was 86.4% in the PT group and 86.2% in the LSM group ( P  = 0.878), while the 5-year overall survival rates were 50.0% and 48.3%, respectively ( P  = 0.68). In our experience, replacement of LSM by a PT approach in oral carcinoma was associated with decreased rates of late complications such as pseudarthrosis, fistula, and trismus, without any difference in oncological outcomes.